Karnali Tourism: Natural Attractions - Badal, B. P. (Research Nepal Journal of Development Studies, 2022)
“Karnali Tourism: Natural Attraction” is a general literature review of referenced sources. It is a collection of facts about pristine or virgin tourist attractions in the Karnali province of Nepal. Its natural attractions accommodate a wonderland to visit and enjoy life. The paper is focused on the natural attractions of Karnali Province. To generalize the facts of the Nature of Karnali from a tourism perspective a study has been conducted. It is the scientific but descriptive literature review of available sources. The paper will be a guideline for field researchers of tourism in Karnali. Nepal is one of the pristine centers of tourism attraction. Nepal’s most beautiful natural attraction is Karnali. Karnali tourism is a set of distinctive material, intellectual, spiritual, and emotional features of society. It encompasses arts and architecture, historical and cultural heritage, literature, music, and the living cultures with their lifestyles, value systems, beliefs, and traditions of Karnali. Karnali is one of the most beautiful landscapes. It is still a virgin in many aspects of exploration. It is one of the most visiting places in life.